Permeability, tortuosity, and attenuation of waves in porous materials = Dyfuzyjność, krętność i tłumienie fal w materiałach porowatych - Wilmański, Krzysztof (1940-2012) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper contains a consistent presentation of the construction of a linear poroelastic model and its applications in the theory of acoustic waves. The main purpose of this presentation is the discussion of material parameters describing the diffusion. This concerns particularly the permeability and tortuosity.
Keywords: ośrodki porowate; dyfuzja; krętność; przepuszczalność; fale akustyczne; porous media; diffusion; permeability; tortuosity; acoustic waves